INTERPRETASI TOKOH MELALUI POSTER FILM JALAN YANG JAUH JANGAN LUPA PULANG - Putra, Dhika Purnama; Saefudin, Ahmad Thabathaba’I (Narada : Jurnal Desain dan Seni, 2025)
Poster as one of the promotional tools that combine text and images, have an important role in film marketing strategies. Posters not only provide information, but also create emotional impressions through visual signs. In this context, posters function as a medium to convey the atmosphere and main theme of the film to potential viewers. For example, the film "Jalan Yang Jauh Jangan Lupa Pulang". This film poster displays emotional elements and visual signs that are characteristic of the characters, so it becomes an object of semiotic research to understand the interpretation of the characters in the poster. The purpose of this study is to analyze the interpretation of each character through the visual signs of the film poster. This study is expected to understand how the interpretation of the characters through the film poster "Jalan Yang Jauh Jangan Lupa Pulang" using qualitative methods and Roland Barthes semiotics.